Web Based Information System in Coffee Cirengot 33 Bandung - Endang Amalia; Rendi (TEPIAN, 2020)
This study aims to help solve the problem Reservation of cirengot coffee shop places is still done manually and transaction reports are still manual on 33 cirengot roads in the city of Bandung where the study was conducted. The background of writing this report is because there are several problems that exist around ordering food and beverages are still manual and transaction reports are still manual. Research data collection through the process of library study and interview process. The research method used is the research action design and the development method is Prototype. While modeling the system using Unified Modelling Language is expected that all three can maximize the desired results. Research conducted includes the creation of a website-based coffee shop information system covering several factors, namely the data management system starting from the owner, employee, financial statements, income, expenses and also there is the preparation of financial reports. It is hoped that the development of web-based information systems can overcome the problems that exist in the Bandung Cirengot coffee shop.